ANALISIS EFEKTIVITAS MAL PELAYANAN PUBLIK (MPP) DALAM PENYELENGGARAAN PELAYANAN PERIZINAN BERUSAHA DI KABUPATEN BATANG - Yoga Restu Nur Roqim; Titik Djumiarti; Ida Hayu Dwimawanti (Journal of Public Policy and Management Review, 2023)
MPP is an expansion of integrated service functions that provide various types of public services in one location. The MPP aims to provide convenience, speed, affordability, safety and comfort to the public in obtaining services, and is expected to increase the ease of doing business, but in the implementation of the Batang Regency MPP found a number of problems indicating the ineffectiveness of the Batang Regency MPP, especially in the implementation of business licensing services. This study aims to analyze the effectiveness of the MPP in administering business licensing services in Batang Regency along with the supporting and inhibiting factors for this effectiveness. This research is important, considering the potential for promising business and industrial development must be supported by ease of business licensing which is realized through the effective implementation of MPP Batang Regency. This study uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation, as well as using domain analysis. The results showed that MPP Batang Regency in the implementation of licensing services was quite effective based on three indicators of organizational effectiveness by Duncan, namely goal attainment, integration, and adaptation, while the supporting and inhibiting factors for effectiveness were analyzed through four characteristics that determined organizational effectiveness by Steers, namely organizational characteristics, environment, employees, and management. The advice given is the need for regulations governing all services and OPD in the Batang Regency MPP under the control of the Batang Regency MPP organizer coordinator, the need for a massive outreach activity program about the importance of owning business licenses, the need for building expansion, the need for repair and development as well as massive outreach to the public about the online service system